2013
DOI: 10.1186/1471-2377-13-160
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis pathway for patients with amyotrophic lateral sclerosis: retrospective analysis of the US Medicare longitudinal claims database

Abstract: BackgroundInitial symptoms of amyotrophic lateral sclerosis (ALS) are often subtle and can delay diagnosis. This exploratory analysis was conducted to better characterize the pre-diagnosis pathway undertaken by patients with ALS in the US Centers for Medicare & Medicaid Services Medicare longitudinal claims database.MethodsQuarterly Medicare claims data were analyzed to determine the pre-diagnosis pathway for an ALS patient cohort that included patients aged ≥ 65 years with ≥ 2 ALS claims (International Classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 15 publications
3
42
1
3
Order By: Relevance
“…The distribution of site of onset of disease in our cohort of C9Pos patients closely mirrored that of C9Neg patients and was typical of other ALS cohorts. 24 The racial makeup of both groups was largely Caucasian, 25 which reflects our patient population. The equal distribution of men and women in the C9Pos group may reflect the autosomal dominant inheritance of the C9orf72 expansion mutation.…”
Section: Demographic and Clinical Information Acquisitionmentioning
confidence: 99%
“…The distribution of site of onset of disease in our cohort of C9Pos patients closely mirrored that of C9Neg patients and was typical of other ALS cohorts. 24 The racial makeup of both groups was largely Caucasian, 25 which reflects our patient population. The equal distribution of men and women in the C9Pos group may reflect the autosomal dominant inheritance of the C9orf72 expansion mutation.…”
Section: Demographic and Clinical Information Acquisitionmentioning
confidence: 99%
“…Note that even though patients with clinically possible ALS initially showed only mild symptoms mainly with lower motor neuron signs, they showed significantly higher ADCs than patients with CSM including those with CSA. On the other hands, it has been reported that the median time to diagnose ALS for patients with limb onset was longer than that for patients with bulbar onset [3], although 13/19 ALS patients with limb onset who did not develop bulbar symptoms initially were also observed to have elevated ADCs in the corticospinal tracts in our study. We believe that evaluating the ADCs in the intracranial corticospinal tracts is useful for distinguishing ALS from CSM in the early stage of the disease.…”
Section: Discussionmentioning
confidence: 59%
“…Fifty percent of patients with amyotrophic lateral sclerosis (ALS) have cervical spondylotic myelopathy (CSM) as a complication [1,2]. Although, bulbar symptoms are meaningful for diagnosing ALS, a large retrospective cohort of ALS showed that patients with ALS developing bulbar symptoms at onset were only 25% [3]. Because most patients with ALS do not develop bulbar signs and symptoms at onset, distinguishing them from patients with CSM is sometimes difficult, especially from those with cervical spondylotic amyotrophy (CSA) who do not show sensory symptoms [4].…”
Section: Introductionmentioning
confidence: 99%
“…Bu noktada kas gücünü değerlendiren klinik testler hastanın yürüme potansiyeli hakkında yetersiz kalır ve sayısal analiz gerekliliği ortaya çıkar. [9][10][11] Kas güçsüzlüğü ile karşılaşılan durumlarda birçok adaptasyon mekanizması devreye girer. Öncelikle artmış motor kontrol vasıtası ile enerji tasarrufu sağlanır ve normale yakın yürüme biçimine ulaşılır.…”
Section: Kas Güçsüzlüğüunclassified